Prognostic factors in patients with localized and metastatic alveolar rhabdomyosarcoma. A report from two studies and two registries of the Cooperative Weichteilsarkom Studiengruppe CWS - Ewa Koscielniak; Sabine Stegmaier; Gustaf Ljungman; Bernarda Kazanowska; Felix Niggli; Ruth Ladenstein; Bernd Blank; Erika Hallmen; Christian Vokuhl; Claudia Blattmann; Monika Sparber‐Sauer; Thomas Klingebiel (Cancer Medicine)
Abstract Background The histologic classification of rhabdomyosarcoma (RMS) as alveolar (aRMS) or embryonal (eRMS) is of prognostic importance, with the aRMS being associated with a worse outcome. Specific gene fusions (PAX3/7::FOXO1) found in the majority of aRMS have been recognized as markers associated with poor prognosis and are included in current risk stratification instead of histologic subtypes in localized disease. In metastatic disease, the independent prognostic significance of fusion status has not been definitively established. The objective of this analysis was to evaluate survival outcomes of patients with localized and metastatic aRMS and its association with fusion status and subtype (PAX3/7::FOXO1, FOXO1 break), and clinical prognostic factors. Methods A total of 470 patients with aRMS ≤21 years of age enrolled in two CWS‐trials and two registries was eligible for the analysis. Results The 5‐year event‐free survival (EFS) and overall survival (OS) rates for all patients with localized vs. metastatic tumors were: 56% and 65% vs. 18% and 22%, respectively. Of the 368 (78%) tumors tested, specific fusion was found in 330 (90%), considered “fusion positive” FP (PAX3::FOXO1 in 280, PAX7::FOXO1 in 49, FOXO1 break in 59 tumors). In patients with localized tumors, univariate analysis revealed that clinical group, tumor invasiveness (T1 vs.T2), regional lymph node involvement (N0 vs. N1) and FOXO1 fusion were significantly associated with EFS and OS, tumor size and PAX variant with OS only. In patients with metastatic aRMS, age, bone/marrow (B/BM) metastases, FOXO1 fusion and PAX variant were associated with EFS and OS, T status with OS only. Multivariate analysis identified PAX3::FOXO1 fusion as an independent adverse prognostic factor for EFS in patients with localized disease and for EFS and OS in patients with metastatic disease, B/BM metastases for EFS. Conclusion PAX3::FOXO1 fusion should replace FOXO1 fusion as an adverse prognostic factor in risk stratification. The prognostic relevance of PAX7::FOXO1‐positive and FOXO1 fusion negative aRMS, along with the clinical factors described in this report, allows further refinement of risk assessment of patients with localized and metastatic aRMS.